β-Cell Failure in Type 2 Diabetes: A Case of Asking Too Much of Too Few? - Costes, Safia (American Diabetes Association, 2013)
The islet in type 2 diabetes (T2DM) is characterized by a deficit in β-cells, increased β-cell apoptosis, and extracellular amyloid deposits derived from islet amyloid polypeptide (IAPP). In the absence of longitudinal studies, it is unknown if the low β-cell mass in T2DM precedes diabetes onset (is a risk factor for diabetes) or develops as a consequence of the disease process. Although insulin resistance is a risk factor for T2DM, most individuals who are insulin resistant do not develop diabetes. By inference, an increased β-cell workload results in T2DM in some but not all individuals. We propose that the extent of the β-cell mass that develops during childhood may underlie subsequent successful or failed adaptation to insulin resistance in later life. We propose that a low innate β-cell mass in the face of subsequent insulin resistance may expose β-cells to a burden of insulin and IAPP biosynthetic demand that exceeds the cellular capacity for protein folding and trafficking. If this threshold is crossed, intracellular toxic IAPP membrane permeant oligomers (cylindrins) may form, compromising β-cell function and inducing β-cell apoptosis.